Psychological Stress in Relation to Achievement among Male and Female Science Students - Narendra Kumar,; Rajive Kumar, (JOURNAL OF INDIAN EDUCATION, 2011)
This study attempts to assess the psychological stress among male and female senior secondary science students in relation to achievement. A sample of 631 (419 male and 212 female) senior secondary science students was randomly selected from different types of institutions of Meerut district. They were administered Psychological Stress Scale for Science Students developed by researchers themselves which measures 12 dimensions of psychological stress. Results showed that both male and female science students significantly differed on psychological stress and achievement. There was also significant relationship between psychological stress and achievement of male and female science students.